Fatal Infection Caused by Chromobacterium violaceum: A Case Report from a Tertiary Care Hospital in Bangladesh. (23rd April 2019) - Sharmin, Sadia; Jahan, Aflatun Akter; Kamal, S. M. Mostofa; Sarker, Protim
Abstract : Chromobacterium violaceum is a Gram-negative bacterium, found in tropical and subtropical regions. C . violaceum infection rarely occurs, but once occurs, it is associated with significant mortality due to severe systemic infection. Since the first human case from Malaysia in 1927, >150 cases of C . violaceum infection have been reported worldwide. We have described here a fatal case of C . violaceum infection in a tertiary care hospital in Dhaka, Bangladesh. To the best of our knowledge, this is the first case of C . violaceum infection in Bangladesh.